Perencanaan Strategi Sistem dan Teknologi Informasi pada PT. Tripuri Mitra Nobelindo - Pelawi, Dewan; Franky, Franky; Willy, Charles; Irwanza, Bobby (Bina Nusantara University, 2011)
Competitions faced by companies are some obstacles in achieving the business objectives to maintain the company's growth and survival. The use of information technology trend requires companies to use it in order to compete with competitors. Strategic planning of information system (IS) and information technology (IT) which refer to business strategy should be customized to the company's business processes. The process of finding a future application portfolio is preceded by the discovery of business strategy, IS/IT strategy managemen and IT strategy. The method used is the strategic planning of information system and information technology of Ward and Peppard. The discovery of business strategy through internal and external analysis of the company is done using tools: PEST, SWOT, Porter's five competitive model, Value chain, and CSF. The analysis of the current information systems helps determine the proposed IS and IT plan. The result achieved is strategic system plan and information technology that are appropriate to the company in achieving its business goals.